If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -10 = 3(x + -2) + 5(x + -1) Reorder the terms: -10 + 7x = 3(x + -2) + 5(x + -1) Reorder the terms: -10 + 7x = 3(-2 + x) + 5(x + -1) -10 + 7x = (-2 * 3 + x * 3) + 5(x + -1) -10 + 7x = (-6 + 3x) + 5(x + -1) Reorder the terms: -10 + 7x = -6 + 3x + 5(-1 + x) -10 + 7x = -6 + 3x + (-1 * 5 + x * 5) -10 + 7x = -6 + 3x + (-5 + 5x) Reorder the terms: -10 + 7x = -6 + -5 + 3x + 5x Combine like terms: -6 + -5 = -11 -10 + 7x = -11 + 3x + 5x Combine like terms: 3x + 5x = 8x -10 + 7x = -11 + 8x Solving -10 + 7x = -11 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -10 + 7x + -8x = -11 + 8x + -8x Combine like terms: 7x + -8x = -1x -10 + -1x = -11 + 8x + -8x Combine like terms: 8x + -8x = 0 -10 + -1x = -11 + 0 -10 + -1x = -11 Add '10' to each side of the equation. -10 + 10 + -1x = -11 + 10 Combine like terms: -10 + 10 = 0 0 + -1x = -11 + 10 -1x = -11 + 10 Combine like terms: -11 + 10 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1
| 95=-47-4(t+6) | | -2x+9y=-6 | | 10-6x-9x+3= | | 8(2c+2)= | | 27(x-1)=3(2x) | | 8y+56=15y | | 20-2v=3v | | 90(x+4)+15(x)=4x(x+4) | | 30+x=7x | | 3y=-15x+270 | | -38+8x=2(8x+1)+8 | | t=0.25(i-32720)+4867.5 | | 4x^2-89x-360=0 | | 6v-5v=3v+8 | | V^2-121=0 | | x+1+x+9=50 | | 36+7v=13v | | 10x-5y+6=6 | | 3(1+6m)=-16-m | | 0.03-0.4x=1.85 | | 7-3(9-x)=16 | | 2(a+6)=5+9 | | 3n^3+10n+16=8 | | 2z^2+5z+3= | | 2b+8(2b-3)=-3(-5b-6) | | -n-21=3(6n-7) | | -2x+19+5x-11=x | | 16+7yi=-8x+i | | 2x-2=x^2-5 | | 4(x+4)=4(x-2) | | 3x-7=3x+1-1 | | 2z^2+9z+10= |